Training on the Use of Learning Management Systems as an Effort to Develop Learning Media - Sopian Alviana; Bobi Kurniawan (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of this community service is to develop teachers’ understanding in using Learning Management System (LMS). The technique or method of approach used is to provide training on the use of LMS for teachers as an auxiliary medium for the teaching and learning process. It is hoped that this community service will be able to improve the ability and understanding of teachers in using LMS used in schools. So that the teachers become capable and proficient in using every feature in the LMS. From the results of the service program, 80% of respondents already understand the use of the LMS program for learning media.